2006
DOI: 10.1080/10473289.2006.10464442
|View full text |Cite
|
Sign up to set email alerts
|

Interaction Effects of Metals and Salinity on Biodegradation of a Complex Hydrocarbon Waste

Abstract: The presence of high levels of salts because of produced brine water disposal at flare pits and the presence of metals at sufficient concentrations to impact microbial activity are of concern to bioremediation of flare pit waste in the upstream oil and gas industry. Two slurry-phase biotreatment experiments based on three-level factorial statistical experimental design were conducted with a flare pit waste. The experiments separately studied the primary effect of cadmium [Cd(II)] and interaction effect between… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 6 publications
0
2
0
Order By: Relevance
“…The solubility of high molecular weight PAHs such as benzo[a]pyrene was also sensitive to small changes in salinity [40]. Amatya et al [41] found that with increases in salinity, the ionic strength would rise and induced more PAH sorption. The present study showed that the high salinity (20 ppt) enhanced the Phe sorption onto sediment and decreased the bioavailability of Phe in the aqueous phase but salinity effect was not obvious at salinity lower than 20 ppt.…”
Section: Discussionmentioning
confidence: 97%
“…The solubility of high molecular weight PAHs such as benzo[a]pyrene was also sensitive to small changes in salinity [40]. Amatya et al [41] found that with increases in salinity, the ionic strength would rise and induced more PAH sorption. The present study showed that the high salinity (20 ppt) enhanced the Phe sorption onto sediment and decreased the bioavailability of Phe in the aqueous phase but salinity effect was not obvious at salinity lower than 20 ppt.…”
Section: Discussionmentioning
confidence: 97%
“…Like most other organisms, microorganisms are susceptible to high concentrations of heavy metals (Giller et al 1998 ; Mattila et al 2007 ). The effects of heavy metals on biodegradation of environmental pollutants have been studied, mostly for separate hydrocarbons (Ma et al 2018 ), mixtures of hydrocarbons (Amatya et al 2006 ), diesel oil (Sprocati et al 2012 ), polychlorinated biphenyls (PCBs), perchloroethene (PCE) (Lu et al 2020 ), and phenanthrene (Wong et al 2005 ). The effects of operational conditions such as pH, temperature, loading, phosphate amendment, and light, on SCN − biodegradation, have also been investigated (Kantor et al 2015 , 2017 ; Lay-Son and Drakides 2008 ; van Zyl et al 2017 ; Watts et al 2017a , 2019 ).…”
Section: Introductionmentioning
confidence: 99%